(untitled) (Ozone Therapy Global Journal, 2020)
Introduction: Facial palsy is an everyday condition. The majority of cases are included on condition of generally idiopathic etiology or Bell´s Palsy. Generally constitue a bening pathology, but with variable recovery, and the risk of effects. The treatment combines physics and pharmaceutical methods, and, sometimes, rehabilítate surgery and neuromuscular therapy. Ozone therapy is a treatment that does not cause side effects, allergies, interaction with other drugs, is easy to apply and low cost which makes it an excellent therapy. Objetive: To present 5 clinical Bell Palsy´s cases treated with ozone therapy as a complementary way with physical therapy. Material and methods: 5 patients were treated by local infiltrations with ozone in a concentration of 10 a 20 µgr/mL, once every 7 days, a mínimum 4 times and a máximum depending on the clinic improvement. Results: High improvement or total recovery were observed in a period of time of 4 to 5 weeks. Conclusion: Ozone therapy may constitute a good choice in the treatment due to the effects noticed in improving symptomatology.